2009
DOI: 10.1111/j.1600-0706.2009.16753.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distributions of tree species in a subtropical forest of China

Abstract: The spatial dispersion of individuals in a species is an important pattern that is controlled by many mechanisms. In this study we analyzed spatial distributions of tree species in a large‐scale (20 ha) stem‐mapping plot in a species‐rich subtropical forest of China. O‐ring statistic was used to measure spatial patterns of species with abundance >10. Ω0–10, the mean conspecific density within 10 m of a tree, was used as a measure of the intensity of aggregation of a species. Our results showed: (1) aggregated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 40 publications
(58 reference statements)
12
77
1
4
Order By: Relevance
“…Because limited resources could not meet the demands of all trees, "self-thinning" was likely triggered; this process caused the distributions to become increasingly random and regular (Li, 2010). We concluded that the results were consistent with those of other studies on spatial patterns (Li et al, 2009;Zhu et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…Because limited resources could not meet the demands of all trees, "self-thinning" was likely triggered; this process caused the distributions to become increasingly random and regular (Li, 2010). We concluded that the results were consistent with those of other studies on spatial patterns (Li et al, 2009;Zhu et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…One is a dynamic approach where the factors affecting changes in species richness are investigated using data collected from the forests at different successional stages [1]. Another is a statistical approach where the factors are inferred from the existing stand structure and spatial pattern using the data collected in a plot [6]. For example, spatial patterns (aggregation, random, and regular) are usually used to interpret species assembly and coexistence [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Armesto et al 1986), there is little information on multi-species patterns of dispersion at diff erent scales. Li et al (2009) found that 92% of species were aggregated at scales <50 m, and Condit et al (2000) found similar results for scales <30 m. Th ese scales correspond to our patterns B and C, but in the PEIC plot 25% of the most abundant species were aggregated at scales >70 m. Clumped distributions are generally the result of association to discrete habitats, patterns of seed dispersal, interspecifi c interactions (e.g. competition, facilitation), and/or expanding or contracting distributions (Hutchings 1997;Valencia et al 2004;Law et al 2009;Li et al 2009), whereas large clumps can be related to environmental heterogeneity.…”
Section: Spatial Distributionmentioning
confidence: 99%